Effects of oral probiotic supplements on vaginal microbiota during pregnancy: a randomised, double‐blind, placebo‐controlled trial with microbiome analysis. (1st April 2019) - Husain, S; Allotey, J; Drymoussi, Z; Wilks, M; Fernandez‐Felix, BM; Whiley, A; Dodds, J; Thangaratinam, S; McCourt, C; Prosdocimi, EM; Wade, WG; de Tejada, BM; et al.
Abstract : Objective: To determine the effects on the vaginal microbiota of an oral probiotic preparation administered from early pregnancy. Design: Randomised, double blind, placebo‐controlled trial. Setting: Four maternity units in the UK. Population: Women aged 16 years or older recruited at 9–14 weeks' gestation. Methods: Participants were randomly allocated to receive oral capsules of probiotic containing Lactobacillus rhamnosus GR‐1 and Lactobacillus reuteri RC‐14 each at 2.5 × 10 9 colony‐forming units (CFUs) or placebo once daily from recruitment until the end of pregnancy. Main outcome measure: Rates of bacterial vaginosis (BV, defined as Nugent score ≥7) at 18–20 weeks' gestation compared by logistic regression adjusted for possible confounders. Results: The primary analysis included 78% (238/304) of participants who initially consented (probiotic group 123, placebo group 115). Of these participants, 95% (227/238) reported an intake of 93% or more of the required number of capsules. The rates of BV did not differ between groups at 18–20 weeks' gestation (15% (19/123) in the probiotic group vs. 9% (10/115) in the placebo group, adjusted odds ratio 1.82, 95% confidence interval 0.64–5.19). There were also no differences between the groups in the proportion of women colonised with the probiotic strains, Escherichia coli, group B streptococci or other vaginal microbiota. There were no differences in the alpha diversity or composition of the bacterial communities between or within the probiotic and placebo groups at 9–14 and 18–20 weeks' gestation. Conclusions: Oral probiotics taken from early pregnancy did not modify the vaginal microbiota. Tweetable abstract: The oral probiotic preparation used in this study does not prevent BV in pregnant women. Tweetable abstract: The oral probiotic preparation used in this study does not prevent BV in pregnant women.